Image of Kaliningrad (Königsberg) in British media: Образ Калининграда (Кенигсберга) по материалам британской прессы - Utkina, Larisa (Przegląd Wschodnioeuropejski, 2020)
The article builds up the image of Kaliningrad (Königsberg) on the basis of publications in modern British media (BBC News, the Times and several others) of the last 3 decades. The articles were selected by key-words Search (Kaliningrad/Königsberg/Kaliningrad- Königsberg). This method gave 70 stories from BBC News and 65 articles from The Times (some articles from the Guardian, the Independent and the Sun are also included). The techniques of creating the image with linguistic means are described. The historical, social, political, economic and cultural aspects of inculcating the image into the readers’ minds are dwelt on. The main topics discussed in the publications are: 1) World War 2; 2) German heritage in the city (I. Kant, etc.); 3) downs and ups in the development of the region; 4) military issues and worries of neighbor countries (Poland, Lithuania); 5) Soccer World Cup 2018 (Kaliningrad was one of its locations). Several other topics are also covered. The analysis, in general, shows that the image created does not look very positive, except for the fantastic atmosphere during World Cup.